TRADITIONAL KNOWLEDGE OF THE MEITEIS IN THE MANAGEMENT OF FLOOD DISASTER - Devi, H. Chitra; Singh, Th. Rabikanta; Pungfa, Ngathem (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Traditional knowledge of a people is transmitted through generations as a part of their livelihood schemas within the ambit of their worldview. It exhibits a deep understanding and ability to cope problems in their own ways. The Meiteis as an autochthone of Manipur, India also inherit traditional knowledge for responding disasters and managing the unavoidable hazards as a geo-cultural community depending on their environmental resources. It is an attempt to gather diligently the traditional knowledge about the flood disaster in context based on the scientific investigation through in-depth interview, observation, and case study methods. It assesses before, during and after disaster of flood and suggests adequate recognition of the local practices of the human-nature interaction in the national calamity database of climate change.